RETROFITTING AND DACTILITY OF REINFORCED CONCRETE BEAMS USING AN EXTERNAL REINFORCEMENT METHOD - Novita Ike Triyuliani; Sri Murni Dewi; Lilya Susanti (Jurnal Rekayasa Sipil dan Lingkungan, 2019)
The innovations strengthening building structures are important topics. Failure in structures such as beams and columns due to time, re-functions of a building, even initial design errors that are weak or lack the safety factor of a building structure. External reinforced concrete beams are one of the beams currently being developed. It is a concrete block with reinforcement of steel reinforcement on the outer (external) of the beam. This study aims to determine the index of increasing beam strength and ductility after retrofitting external steel reinforcement, which has the dimension of beams 15 x 15 x 100 cm, repeating 12 pcs, with external reinforcement each 6 pcs 2Ø6 and 3Ø6. The results from this study are an increasing the index of beam flexural strength after retrofit with external steel reinforcement. Meanwhile, beams after retrofit with 2Ø6 external steel have an average increase index of 1.25 and 1.21 while for external steel 3Ø6 are 1.29 and 1.60 respectively. The ductility depends on the value of ultimate load and maximum deflection that occurs, where the ductility value for the comparison of each specimen experiences a reduction in the average ductility value with 2Ø6 external steel which is 37.74% and 70.95% while with 3Ø6 external steel is 61,65% and 60.62%. Berbagai inovasi upaya peningkatan kekuatan struktur bangunan telah menjadi bahasan yang penting. Kegagalan pada struktur seperti balok dan kolom karena umur, alih fungsi suatu bangunan, bahkan kesalahan desain awal yang lemah atau kurang memenuhi faktor keamanan suatu struktur bangunan. Balok beton bertulangan eksternal adalah salah satu balok yang sedang dikembangkan pada saat ini, yaitu balok beton dengan perkuatan tulangan baja di sisi terluar (eksternal). Penelitian ini bertujuan untuk mengetahui indeks peningkatan kekuatan balok dan daktilitas setelah dilakukan perbaikan menggunakan tulangan baja eksternal, dengan dimensi balok 15 × 15 × 100 cm berulang 12 buah, penambahan tulangan baja eksternal masingmasing 6 buah 2Ø6 dan 3Ø6. Hasil yang didapat dari penelitian ini adalah indeks peningkatan kekuatan lentur balok setelah dilakukan perbaikan menggunakan tulangan baja eksternal. Dimana balok setelah dilakukan perbaikan dengan baja eksternal 2Ø6 memiliki indeks peningkatan rata-rata 1,25 dan 1,21 sedangkan untuk baja eksternal 3Ø6 masing-masing 1,29 dan 1,60. Daktilitas tergantung dari nilai beban ultimit dan lendutan maksimum yang terjadi, dimana nilai daktilitas untuk perbandingan tiap benda uji mengalami reduksi nilai daktilitas rata-rata dengan baja eksternal 2Ø6 yaitu sebesar 37,74% dan 70,95% sedangkan dengan baja eksternal 3Ø6 sebesar 61,65% dan 60,62%.